Margaret Atwood : The Open Eye - Kozakewich, Tobi, 1975-; Moss, John, 1940- (Book collections on Project MUSE., 2006)
Margaret Atwood enjoys a unique prominence in Canadian letters. With over thirty books to her credit, in genres ranging from children's writing to dystopic novels, she is as creatively diverse as she is internationally acclaimed. Her success, however, has been double-edged: the very popularity that makes her such a prominent figure in the literary world also renders her vulnerable to claims of being a "sell-out," as she relates in her Empson lectures. The Open Eye negotiates the space between these positions, acknowledging Atwood's remarkable achievement while considering how it impacts on national politics and identity. The range of perspectives in this volume is stimulating and enlightening. The Open Eye begins with a focus on Atwood as she presents herself and is presented in Canada and abroad, and then proceeds to consider, more broadly, the intersection of life and literature that Atwood's works and persona effect. It offers fresh insight into Atwood's early writing, redresses the critical void regarding her poetry and shorter prose pieces, and provides a critical base from which readers can assess Atwood's most recent novels. A common thread throughout these essays is the recognition of Atwood's importance in the literary realm in general, and in Canadian literature more particularly